(untitled) (The Pretoria Student Law Review, 2021)
In this investigation, I will compare and contrast the UNCITRAL model law on cross-border insolvency law (hereafter referred to as ‘UNCITRAL model law’) with the EU Insolvency Regulation against the backdrop of various sources or dispensations of cross-border insolvency law. In this comparison, I will highlight the similarities and differences between the two, as well as discuss the other sources in depth, as they largely inform my research. My main aim in including the other sources in this comparative study is to provide deeper insight into these two sources of international cross-border insolvency law, as provided for by academics and sages in the field of insolvency law. These other sources include legislation, common law, treaties and regional dispensations.